Layanan Konseling Online Dalam Kerangka Bimbingan Dan Konseling Komprehensif: Peluang, Tantangan, Dan Isu Etika Di Era Digital - Bahtiar, Apriadi; Prasetya, Akhmad Fajar; Hartanto, Dody; Martaningsih, Sri Tutur (CV. SINAR HOWUHOWU, 2025)
The rapid development of digital technology has driven significant transformations in guidance and counseling services, one of which is the implementation of online counseling. This service offers substantial opportunities to enhance the accessibility and flexibility of counseling services; however, it also raises various challenges and complex ethical issues. This study aims to examine online counseling services within the framework of Comprehensive Guidance and Counseling by focusing on opportunities, challenges, and ethical issues in the digital era. This research employed a qualitative approach using a literature review method. Data were collected from relevant sources, including national and international journal articles, scholarly books, and policy documents related to online counseling and Comprehensive Guidance and Counseling. Data analysis was conducted using content analysis to systematically integrate conceptual and empirical findings. The results indicate that online counseling has strong potential to strengthen all components of Comprehensive Guidance and Counseling, namely basic services, responsive services, individual planning, and system support. Nevertheless, its implementation continues to face challenges, particularly related to counselors’ digital competence, technological infrastructure gaps, and the high risk of ethical violations, especially concerning confidentiality and data security. Therefore, the integration of online counseling within the Comprehensive Guidance and Counseling framework requires strengthening counselors’ professional competencies, establishing clear ethical regulations, and providing adequate system support to ensure that counseling services are delivered safely, ethically, and sustainably in the digital era.